Técnica TDS para pozos horizontales multifracturados en yacimientos de lutitas gasíferas (2018)
This investigation the pressure response and its derivative for a horizontal multi-fractured horizontal well obtained from an analytical simulator, which was based on a mathematical model proposed in 2012, which included the adsorption and desorption of the shale are analyzed. The pressure response of the simulator is governed by the following parameters: the dimensionless interporosity flow coefficient (λ), the dimensionless storativity ratio (ω), the adsorption and desorption coefficient (σ), the fracture length (xf) and the number of fractures (M). Different pressure analyzes are made, varying different parameters, where points and characteristic lines are identified that allow obtaining equations for the calculation of λ, ω and xf. Finally, the TDS methodology (Tiab´s Direct Synthesis Technique) is extended and verified with synthetic examples.